The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0037-0738(00)00177-9
|View full text |Cite
|
Sign up to set email alerts
|

Christmas Island lagoonal lakes, models for the deposition of carbonate–evaporite–organic laminated sediments

Abstract: The atoll of Christmas Island (now known as Kiritimati) in the Kiribati Republic (Central Pacific) lies at about 2°N in the intertropical convergence zone. Much of the surface area of the atoll (ca. 360 km2) is occupied by numerous lakes in which carbonate, evaporite (calcium sulfate, halite) and organic layers are deposited. Observations suggest that deposition of these different laminae is controlled by climatic and biologic factors. It is thought that periodic climatic variations, such as El Niño-Southern O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 9 publications
(12 reference statements)
5
94
0
1
Order By: Relevance
“…In fact, the formation of dolomite in this closed lacustrine environment would have required episodic flooding by fresh water (Folk and Land, 1975;Trichet et al, 2001), allowing saline brines to be periodically mixed with fresh water in a low lake system. The salinity drops drastically, but the Mg/ Ca ratio remains almost as high as it was initially.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the formation of dolomite in this closed lacustrine environment would have required episodic flooding by fresh water (Folk and Land, 1975;Trichet et al, 2001), allowing saline brines to be periodically mixed with fresh water in a low lake system. The salinity drops drastically, but the Mg/ Ca ratio remains almost as high as it was initially.…”
Section: Discussionmentioning
confidence: 99%
“…The biogeochemical properties of 'kopara' have been extensively studied with respect to relationships between organic compounds and mineralization processes (Trichet, 1967;De´farge et al, 1985De´farge et al, , 1996De´farge & Trichet, 1990, 1993Trichet & De´farge, 1997;Trichet et al, 2001). The role of proteinaceous compounds and amino acid composition in controlling calcification was studied in deeper layers of 'kopara' mats (Gautret & Trichet, 2005) and other microbialites (Gautret et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Heissenberger et al (1996) observed that particle-associated bacteria exhibit larger envelopes than free-living bacteria, but the fate of these structures was not studied further. The microbial species that may form regular structures, including 'honeycombs' or 'veils,' have been studied mainly in biofilms from cultures or aquatic environments (Dalton et al 1996, Trichet et al 2001, Schaudinn et al 2007 and references therein). Mucus aggregates, comparable to biofilms, could be defined as assemblages of microorganisms and their associated extracellular products attached to an abiotic or biotic surface (Davey & O'Toole 2000).…”
Section: Role Of Microbes In Macroaggregatesmentioning
confidence: 99%